2005
DOI: 10.1136/pgmj.2004.023788
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal subarachnoid haemorrhage: guidance in making the correct diagnosis

Abstract: Background: The natural history of untreated aneurysmal subarachnoid haemorrhage carries a dismal prognosis. Case fatalities range between 32% and 67%. Treatment with either surgical clipping or endovascular coiling is highly successful at preventing re-bleeding and yet the diagnosis is still missed. Methods: Based on the national guidelines for analysis of cerebrospinal fluid for bilirubin in suspected subarachnoid haemorrhage and a review of other available literature this study has compiled guidance in maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…12 Patients with SAH frequently have an additional warning sign, a sentinel headache, described as the occurrence of an undervalued or even ignored oppressive headache in the weeks preceding the aneurysm. [13][14][15] Other symptoms may include nausea and vomiting (77%) as well as loss of consciousness (53%). [13][14][15] Associated symptoms, including syncope, diplopia, and seizure, make SAHs more likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Patients with SAH frequently have an additional warning sign, a sentinel headache, described as the occurrence of an undervalued or even ignored oppressive headache in the weeks preceding the aneurysm. [13][14][15] Other symptoms may include nausea and vomiting (77%) as well as loss of consciousness (53%). [13][14][15] Associated symptoms, including syncope, diplopia, and seizure, make SAHs more likely.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Other symptoms may include nausea and vomiting (77%) as well as loss of consciousness (53%). [13][14][15] Associated symptoms, including syncope, diplopia, and seizure, make SAHs more likely. 12 Figure 1 offers a summary of the signs and associated risk factors that a chiropractor should look for when taking a patient's history.…”
Section: Discussionmentioning
confidence: 99%
“…When CT was performed within 12 h of SAH, one study showed CT failed to detect the SAH for 1.7% of patients [34]. Lumbar puncture (LP) LP may not detect blood during the first 12 h postbleed; however, CT is most sensitive during this time [39,40]. Computed tomography angiography (CTA) a Negative noncontrast CT plus CTA excludes SAH with a >99% probability [35].…”
Section: Cough Sexual Activity Related and Exertional Headachesmentioning
confidence: 97%
“…Photophobia, meningismus, vomiting and syncope soon ensue. If severe headache is the only symptom, the chance of SAH is only 10% 10 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…It is believed that the SAH causes an inflammatory reaction in the basal cisterns of the brain inducing CV, the most common cause of delayed cerebral ischaemia and neurological deficits after SAH. The risk of CV increases with the amount of blood in the subarachnoid space and typically does not begin before the fourth day after SAH and can last for 14-21 days 10,35 . CV can be detected on radiographic imaging and also by bedside transcranial Doppler studies (TCDs).…”
Section: Cerebral Vasospasmmentioning
confidence: 99%